Sustainable food tourism for the preservation of culinary heritage: wine routes in Girona (Catalonia, Spain) and Querétaro (Mexico) - Morales Loya, Marisa (2021)
Sustainable food tourism is developed from experiences based on food heritage to discover not only the products, but also the producers and the physical and human context in which they are located. The protection of food heritage and the promotion of food tourism must be carried out in the context of the Sustainable Development Goals, thus contributing to economic, environmental, cultural and social development. Drawing from a comparative qualitative research, two regions are analyzed, Girona (Catalonia, Spain) and Querétaro (Mexico), which have a food tourism product focused on wine heritage. Ten people with different profiles from the wine and the food tourism sector of the regions are interviewed. The topics of the interview are: (1) Role and professional experience in relation to food tourism and the wine sector, (2) Presence and impact of wine as a culinary heritage of the region, (3) Actions for the development and promotion of food tourism in the wine sector, (4) Implementation of wine as a product that participates in the sustainability of the region, through food tourism. The results present the relationship between tourism and the wine sector of the two regions, responsible production and consumption to guarantee the preservation of heritage and the promotion of strategies for the development of sustainable food tourism.